Al-Mg-Si billets with high extrudability – state of the art and beyond. (2019) - Røyset, Jostein; Tundal, Ulf; Espezel, Cristina; Reiso, Oddvin
Abstract: Within the alloy groups EN-AW6060 and EN-AW6063 a range of alloys termed "High Speed Alloys". have been developed. The underlying metallurgical principles of this development are explained. Further, new technological developments and new experimental discoveries have led to a new, upcoming billet quality, "HP 6xxx". Three different billet qualities, "Standard 6060", "High Speed 6060" and "HP 6060" were compared in a full-scale industrial trial, and the results indicate that the improvement in extrudability of "HP 6060" over "High Speed 6060" is of the same order as the improvement of "High Speed 6060" over "Standard 6060"